2020
DOI: 10.36497/jri.v40i2.103
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum KL-6/MUC1 Level, Neutrophils and Lymphocytes Sputum in Malang Splendid Bird Market Workers

Abstract: Backgrounds: People who work in the bird market have a high exposure risk of air pollution in large numbers, particulate pollutans including organic dust, loose feathers, insects or ticks, food aerosol particles, bird’s excreta (amonia) and various of gram bacteria, fungal and virus. Exposure to particles will stimulate the immune system against harmful pathogens in the form of an inflammatory response. An infection or injury will stimulate secretion of KL-6/MUC1 (Krebs von den Lungen-6 is a high molecular wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Studies in Indonesia investigating KL-6 serum levels among high-risk asymptomatic populations exposed to risk factors related to lung disease are still lacking. An epidemiological study among workers in the bird market showed an increase in average KL-6 serum levels compared to that healthy individuals from the general population (22). Previous studies on the adverse effects of air pollution in Indonesia were limited to investigating the association between air pollutant exposure and demographic and clinical characteristics, such as anthropometric measurements (23)(24).…”
Section: Cite This Asmentioning
confidence: 99%
“…Studies in Indonesia investigating KL-6 serum levels among high-risk asymptomatic populations exposed to risk factors related to lung disease are still lacking. An epidemiological study among workers in the bird market showed an increase in average KL-6 serum levels compared to that healthy individuals from the general population (22). Previous studies on the adverse effects of air pollution in Indonesia were limited to investigating the association between air pollutant exposure and demographic and clinical characteristics, such as anthropometric measurements (23)(24).…”
Section: Cite This Asmentioning
confidence: 99%